Hereditary Thrombophilia in Korean Patients with Idiopathic Pulmonary Embolism - Lee, Mirae; No, Hye Jin; Jang, Shin Yi; Kim, Nari; Choi, Seung Hyuk; Kim, Hojoong; Kim, Sun-Hee; Kim, Hee-Jin; Kim, Duk-Kyung (Yonsei medical journal, 2012)
Hereditary thrombophilia (HT) is a major risk factor for idiopathic pulmonary embolism (iPE) and shows different prevalence among ethnic groups. The prevalence and clinical characteristics of HT in Korean patients with iPE were investigated. Patients with PE on computed tomography (CT) scan were recruited, and those with malignancy were excluded. Patients were divided into iPE and provoked PE (pPE) groups. The presence of HT in the iPE group was assessed by DNA sequencing of the corresponding gene in patients who had low levels of natural anticoagulants. The clinical characteristics of iPE with HT (iPE/HT+) were compared with those of iPE without HT (iPE/HT-) and pPE. Out of 161 patients, 84 patients had iPE and 77 patients had pPE. Among 54 patients in the iPE group whose coagulation profiles were tested, 28 patients were diagnosed with HT (51.9%; 28/54). Compared with the iPE/HT- and pPE groups, the iPE/HT+ group showed the highest proportion of male patients (71.4%; p<0.001); the youngest mean age (44±14 years; p<0.001); and the highest frequencies for history of venous thromboembolism (64.3%; p<0.001), concurrent deep vein thrombosis (75.0%; p=0.021), and adverse clinical outcomes (42.9%, p<0.001). Protein C deficiency was the most common HT. On molecular genetic tests, causative mutation was identified in 13 patients. In this study of Korean patients, about half of the patients with iPE had HT. Patients with iPE and HT were mostly young males with deep venous thrombosis (DVT), previous venous thromboembolism (VTE), and frequent adverse clinical outcomes. Therefore, Korean patients with iPE should be tested for HT.